Reflections on the concept of religion - Díaz Ardila, Jorge Aurelio (Estudios de Filosofía, 2015)
One of the aims in Hegel’s philosophy of religion is to show how the core of Christian doctrine holds the key for a speculative understanding of the kind of truth sought by philosophy since its beginnings. According to Hegel, once thought has historically completed its development, we can understand Christianity as true religion. With this gesture, Hegel broadens the limits of the so–called ’’natural theology’’ and aims to unify theology and philosophy. This paper seeks to exhibit where does this Hegelian gesture becomes inadmissible for Christian theology, namely, the intellectualist character of his proposal as incompatible with Christian voluntarism.